(untitled) (Research, Society and Development, 2020)
Objective: to report the experience of vaccination against H1N1 during the COVID-19 pandemic in Amazonas. Methods: This is a historical research with a qualitative approach, an experience report type. It was carried out through three vaccination actions on the premises of a Public University of Amazonas for teachers and administrative technicians of the Institution. Results: The action carried out in 3 days, resulted in the administration of 425 doses of Tetravalent Influenza vaccine for teachers and students of the nursing, dentistry and medicine courses at UEA. Two methods of vaccination in different locations and formats (Drive-Thru and traditional Immunization Rooms) were used to expand the means of carrying out the immunization. Conclusion: In addition to the description of the vaccination action, for the protection and mitigation of other respiratory syndromes that may hinder the diagnosis of COVID-19, the action described in the study can also contribute and socialize the development of health prevention practices for professionals working directly in the pandemic.